2023
DOI: 10.1002/jpln.202300115
|View full text |Cite
|
Sign up to set email alerts
|

How nano‐iron chelate and arbuscular mycorrhizal fungi mitigate water stress in Lallemantia species: A growth and physio‐biochemical properties

Abstract: BackgroundWater deficit can seriously affect the growth, yield, and biochemical properties of plants; however, the application of nano‐iron chelate and arbuscular mycorrhizal fertilizers in water deficit has been considered one of the most promising methods to improve plant growth and enhance drought tolerance.AimsThis study aimed to investigate the effects of nano‐iron chelated (nFe) fertilizer and arbuscular mycorrhizal fungi (AMFs) on the growth, yield, root colonization, mycorrhizal dependency, water use e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…In the present study, water and the presence of arbuscular mycorrhizal fungi in the maternal plant environment played a significant role in intricately shaping the seed performance, physio-biochemical characteristics, and chemical composition of the next generation [ 1 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, water and the presence of arbuscular mycorrhizal fungi in the maternal plant environment played a significant role in intricately shaping the seed performance, physio-biochemical characteristics, and chemical composition of the next generation [ 1 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with other studies that have demonstrated the benefits of growing mother plants under the influence of mycorrhizal fungi, resulting in higher seed yield and weight [ 54 ]. In the present study, better performance of L. iberica seeds in terms of higher number of achenes, number of seeds, seed weight, and seed size compared to L. royleana can be attributed to the higher nutrient uptake such as phosphorus and nitrogen in L. iberica maternal plant [ 51 ].…”
Section: Discussionmentioning
confidence: 99%